Expanding Global Surgery Services to Include Reduction Mammaplasty Procedures - Chrysis Sofianos, FC Plast Surg (SA), FRCS Plast, FEBOPRAS, FACS; Kyara Kruger, BCMP (WITS) (Plastic and Reconstructive Surgery, Global Open)
Background:. Global surgery is a multidisciplinary field that aims to deliver equitable and improved surgical services. Surgical care has been previously considered to play a limited role in the global burden of disease, in part due to its complexity and associated expense. A functional health system mandates high-quality, accessible, and timely surgical care. Methods:. Literature was reviewed on the role of plastic and reconstructive surgery in global surgery programs, reduction mammaplasty, and quality of life (QoL). Definitions of emergency and essential surgical care were explored to understand which surgical procedures are included in these programs. Reduction mammaplasty is the most researched aesthetic surgery procedure when considering QoL. Results:. The surgical conditions treated by plastic surgeons comprise a large proportion of the global surgical disease burden and disproportionately affect individuals in low- to middle-income countries. Over time, reconstructive surgery has gained equivalence to other surgical fields, partly due to a broader understanding of health; the need for psychological well-being; and the fact that some aesthetic surgery procedures are now considered reconstructive, such as a reduction mammaplasty. Essential surgery comprises low-cost, basic surgical procedures that prevent disability or life-threatening complications and may be performed at the district hospital level. Reconstructive plastic surgery improves QoL in multiple domains, including reduction mammaplasties. Conclusions:. The cost-effectiveness and QoL improvements of reduction mammaplasty have been elucidated; therefore, this can make a real difference for many patients in developing countries. Consideration should be given to expanding the essential surgical care package to include reduction mammaplasty.